O efeito do regime hidrológico do semiárido na composição de espécies durante dominância de cianobactérias em um reservatório tropical - Medeiros, Luciana de Castro (2013)
The potentially toxic cyanobacterial blooms in water bodies are spread across the globe, resulting in the loss of water quality and adverse effects on human health. In arid and semiarid regions, the hydrologic regime characterized by an annual cycle of drought and rain, change the volume and the retention time of the reservoir. Such changes affect the limnological characteristics and causing changes in composition and biomass community of cyanobacteria. The reservoir Cruzeta (Zmax = 8.7 m) is a eutrophic water supply source located in the semiarid tropical (Northeast Brazil). Raised the hypothesis that the hydrological regime of semi-arid tropical is a determining factor in the availability of resources in eutrophic water sources, which influences the composition of dominant species of cyanobacteria. The aim of this study was to analyze the changes in biomass and species composition of cyanobacteria for two annual hydrological cycles and evaluate factors drivers. The study was divided into five distinct periods (dry 2010, rain 2011, dry 2011, rain 2012, dry 2012). The dominant group found in all periods was Cyanobacteria (99% of total biomass), which contributed to the low diversity. The filamentous species Cylindrospermopsis raciborskii was present at both points in almost every study. The colonial species Microcystis panniformis and Sphaerocavum brasiliensis dominated only in periods with lower volumes of water. The diatoms contribute more to the biomass during the period of severe drought. The point near the dam (P1) had phytoplankton biomass larger than the point near the tributary (P2). The dominant species of colonial cyanobacteria lasted until the overflow in P1, and P2 this dominance was until the first rains. The redundancy analysis indicated that physical factors such as light availability and water level were the main factors driving the seasonal succession of phytoplankton. The composition of phytoplankton in spring was alternated by species of filamentous cyanobacteria in conditions of poor stability of the water column, such as Cylindrospermopsis raciborskii, and colonial species under conditions of high stability of the water column, such as Microcystis panniformis and Sphaerocavum brasiliensis. The extremes of torrential rains and severe droughts, governed by the hydrological regime of the semi-arid region led to the availability of resources in the watershed, directing the spatial and temporal dynamics of phytoplankton in the reservoir Cruzeta